Advanced Oxidative Protein Products Drive Trophoblast Cells Into Senescence by Inhibiting the Autophagy: The Potential Implication of Preeclampsia - Li, Zhengjuan; Wang, Shuoshi; Li, Liping (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Advanced oxidation protein products (AOPPs), the novel marker of oxidative stress, have been found to be elevated in preeclampsia (PE). To date, the effect of AOPPs on the senescence of trophoblast cells is still unclear. In this study, we investigated whether AOPPs promoted the senescence of trophoblast cells and explored the underlying mechanisms of AOPPs-induced aging process which may facilitate the progression of PE. Methods: The trophoblast cell line HTR-8/SV neo cells were cultured in the presence of PBS, AOPPs, AOPPs plus an anti-oxidant N-acetyl-L-cysteine (NAC). Or cells were pre-treated with rapamycin (an activator of autophagy), 3-MA (an inhibitor of autophagy), or cyclic pifithrin-α (PFT-α, an antagonist of p53), and then treated with AOPPs. Cellular senescence was analyzed by measuring the levels of senescence-associated β-galactosidase (SA β-Gal), senescence-associated heterochromatin foci (SAHF), and mitochondrial membrane potential (ΔΨm). Cell autophagic flux was analyzed by measuring tandem fluorescence-tagged LC3 reporter (mCherry-EGFP-LC3). Levels of p53, phosphorylated p53 (p-p53), p21, BECN1, p62, p-mTOR and p-p70S6K were measured using western blot. Results: Treatment with AOPPs significantly increased the levels of SA β-Gal and SAHF, and decreased cell ΔΨm compared with the control group. Co-treatment with NAC and AOPPs significantly reversed AOPPs-induced senescene. Pre-treatment with rapamycin or 3-MA significantly inhibited or promoted AOPPs-induced senescene, respectively. In addition, administration of AOPPs significantly decreased the numbers of mCherry+EGFP+ autophagosomes and mCherry+EGFP- autolysosomes in cells compared with cells treated with PBS or rapamycin. Furthermore, AOPPs significantly increased the levels of proteins p-p53, p21, p-mTOR and p-p70S6K compared with the control group. Pre-treatment with PFT-α significantly down-regulated the levels of SA β-Gal, SAHF, p-p53, p21, autophagy related protein BECN1, and significantly up-regulated ΔΨm, p62, autophagosomes and autolysosomes compared with cells only treated with AOPPs. Conclusion: AOPPs may induce trophoblast cell senescence by inhibiting the autophagy process in a p53-mTOR-p70S6K-dependent pathway.